Challenges and Opportunities of Online Education during COVID-19 for Women Teachers - Dharmisthaben Ramanbhai Chauhan (AG Volumes, 2022)
Our lives have been changed forever with COVID -19. This has had a significant effect on the educational system as well. Before the epidemic, the Indian education system relied only on traditional ways of instruction. Teachers were required to change the whole educational system to Online Mode when the COVID-19 attacked the sector. It was not an easy transition to move away from more conventional teaching approaches and toward more contemporary ones. It was a monumental challenge for Indian educators, who are not well-versed in contemporary technology. During the course of this research study, the obstacles and possibilities experienced by women instructors as they transitioned to an online style of teaching, e-learning, will be discussed.